A Conceptual Matrix of Journalism as Research Two Decades after 'Media Wars'. Issue 1 (August 2015) - Pearson, Mark; Patching, Roger; Wilshere-Cumming, Lisa
It is 20 years since John Hartley (1995) positioned journalism as the subject of academic research rather than as a research method in its own right. In 1999, Media International Australia devoted a themed edition to the debate over journalism in the academy ('Media Wars'), which prompted further scholarly discourse over the role and location of journalism as a field of study. This article reassesses that debate in the light of the acknowledgement of journalism studies and journalism creative works in the Excellence in Research for Australia (ERA) system, the use of journalism methods as a research methodology and the development of conceptual paradigms for journalism as research. The article surveys the relationship between journalism and research over the ensuing two decades and proposes a conceptual matrix of the journalism–research nexus.